Antimicrobial properties and toxicity challenges of chlorine dioxide used in alternative medicine - Ruth Dudek-Wicher; Malwina Brożyna; Justyna Paleczny; Beata Mączyńska; Bartłomiej Dudek; Paweł Migdał; Arleta Dołowacka-Jóźwiak; Jędrzej Fischer; Adam Junka (Scientific Reports)
Abstract This study evaluates the in vitro antimicrobial efficacy and cytotoxicity of acidified sodium chlorite (ASC), a source of chlorine dioxide. Despite its controversial promotion in alternative medicine as a cure-all solution, known as "Miracle Mineral Solution" (MMS), the data on its factual medicinal activity is very limited. Therefore, we aimed to elucidate the activity of ASC against biofilms of Staphylococcus aureus, Pseudomonas aeruginosa, Enterococcus faecalis, Streptococcus mutans, Pseudomonas aeruginosa, Escherichia coli, and Lactobacillus sp. or an organic acid (ASC1, ASC2, respectively). The lowest antimicrobial concentration of ASC registered was 0.002992% (29.92 ppm) but did not exhibit stronger antimicrobial activity than polyhexamethylene biguanide. Biofilms of S. mutans and E. coli were the most susceptible to tested formulations. Biofilm formed by L. rhamnosus displayed susceptibility to concentrations lower than the minimum biofilm eradication concentration (0.09575%, 957.5 ppm). In the in vitro cytotoxic assay towards eukaryotic fibroblasts and in vivo model of Galleria mellonella larvae concentration-related increase of cytotoxic effects was observed. Our findings demonstrate that these concentrations of ASC which can effectively eradicate biofilms, also pose potential health risks due to their in vitro and in vivo cytotoxicity. It implies that ASC applied in humans can lead to damage to the mucous membrane of the gastrointestinal tract. This research contributes to the ongoing debate on the safety and efficacy of chlorine dioxide in clinical applications, highlighting the need for precise dosing to avoid mucosal damage in therapeutic contexts.